1994
DOI: 10.1016/0378-1097(94)90578-9
|View full text |Cite
|
Sign up to set email alerts
|

The significance of enteroaggregative Escherichia coli in the etiology of hospitalized diarrhoea in Calcutta, India and the demonstration of a new honey-combed pattern of aggregative adherence

Abstract: Previous studies have identified enteroadherent Escherichia coli that exhibit localized adherence, diffuse adherence and atypical diffuse adherence as diarrhoeagenic agents associated with infantile diarrhoea in Calcutta, India. In this study, a DNA probe specific for enteroaggregative adherence was used to determine the etiological significance of enteroaggregative E. coli in the causation of diarrhoea. From a total of 330 strains of E. coli recovered from 159 cases of acute secretory diarrhoea and 174 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…In this study, the aap and aggR combination was seen in 19 (4.8%) cases and 10 (5.1%) controls, while the aap gene alone was more common in controls (29, 14.6%) than cases (13, 3.3%). Previous reports from India using adherence assays, PCR, and biofilm production have reported a high prevalence of EAEC in cases (Dutta et al, 1999; Kahali et al, 2004; Paul et al, 1994); however, our study found high rates of detection of astA , aap , and aggR in controls, and only the combination of aap , aggR , and AA was significantly associated with disease. There was no overlap between the aafII gene detected in the multiplex DEC PCR and the other 2 EAEC PCRs.…”
Section: Resultscontrasting
confidence: 99%
“…In this study, the aap and aggR combination was seen in 19 (4.8%) cases and 10 (5.1%) controls, while the aap gene alone was more common in controls (29, 14.6%) than cases (13, 3.3%). Previous reports from India using adherence assays, PCR, and biofilm production have reported a high prevalence of EAEC in cases (Dutta et al, 1999; Kahali et al, 2004; Paul et al, 1994); however, our study found high rates of detection of astA , aap , and aggR in controls, and only the combination of aap , aggR , and AA was significantly associated with disease. There was no overlap between the aafII gene detected in the multiplex DEC PCR and the other 2 EAEC PCRs.…”
Section: Resultscontrasting
confidence: 99%
“…We have reported previously that many EAEC strains adhere abundantly to the glass substratum in the HEp‐2 adherence assay, in which bacteria are added to a semi‐confluent monolayer of cells in the presence of mannose and tissue culture medium (Nataro et al ., 1987). In this assay, our prototype EAEC strain 042 adheres abundantly to the glass substratum in a characteristic honeycomb pattern, as described previously (Paul et al ., 1994). To understand this phenomenon better, we observed 042 grown in minimal essential medium with 0.4% glucose (here called high‐glucose MEM) at 37°C, in the absence of HEp‐2 cells, for time points between 1 h and 72 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical features of EAEC illness have been defined from volunteer studies, outbreaks, or sporadic cases, which include watery secretory diarrhea, often with mucus, with or without blood, low‐grade fever, abdominal pain, nausea, and vomiting (Bhan et al ., ; Paul et al ., ; Nataro et al ., ; Adachi et al ., ). Although bloody diarrhea is not a distinctive feature of EAEC illness, Cravioto et al .…”
Section: Clinical Manifestationsmentioning
confidence: 99%